2010
DOI: 10.1007/s10257-009-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards a business process-oriented approach to enterprise content management: the ECM-blueprinting framework

Abstract: In today's digital information age, companies are struggling with an immense overload of mainly unstructured data. Reducing search times, fulfilling compliance requirements and maintaining information quality represent only three of the challenges that organisations from all industry sectors are faced with. Enterprise content management (ECM) has emerged as a promising approach addressing these challenges. Yet, there are still numerous obstacles to the implementation of ECM technologies, particularly fostered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 38 publications
2
60
0
1
Order By: Relevance
“…Based on previous studies, the implementation of ECM enables organizations to enhance information sharing, collaboration and productivity (Alalwan and Weistroffer, 2012;Smith and McKeen, 2003;vom Brocke et al, 2011). As such, the content obtained is more transparent, improve knowledge management in the organization, increasing the ability of communication and interaction as well as reduces the geographical divide.…”
Section: Enterprise Content Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, the implementation of ECM enables organizations to enhance information sharing, collaboration and productivity (Alalwan and Weistroffer, 2012;Smith and McKeen, 2003;vom Brocke et al, 2011). As such, the content obtained is more transparent, improve knowledge management in the organization, increasing the ability of communication and interaction as well as reduces the geographical divide.…”
Section: Enterprise Content Managementmentioning
confidence: 99%
“…Content is obtained from various sources such as structured and digital content, which, if well managed, could assist organizations in making decisions and help to innovate services. Organizations face the challenges in managing digital content since 80% of the content in the organizations are from unstructured digital content such as emails, documents, slide presentations and word files (De Kraker et al, 2013;Herbst and vom Brocke, 2013;O'Callaghan and Smits, 2005;vom Brocke et al, 2011). A study showed that the rate of unstructured content is increasing yearly (Alalwan and Weistroffer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that, in addition to the use of a roadmap, Business Process Modeling / Management (BPM) may bring the necessary strategic focus into the effort (e.g. see [9]). …”
Section: Implications For Implementation Of Ecmmentioning
confidence: 99%
“…The 'Strategy formulation' processed may be utilized for the new decision to set up new businesses, funds distribution policy, whether a particular company needs to expand and exact time to entry into the international markets, etc [8]. It contains the power of execution for the essential managerial process towards the company growth [9]. Strategic leadership mostly influenced by responsible persons capable of taking decision voluntarily to make decisions precisely for the steady growth and prosperity of the target organizations for longterm achievements by maintaining long-term financial stability and improvement [10].…”
Section: Introductionmentioning
confidence: 99%